Gifted students and the specifics of their education at universities (Universal International Scientific Journal, 2026)
This article examines the specifics of teaching gifted students in higher education. It explains the concept of academic giftedness, analyzes the psychological and pedagogical characteristics of gifted students, and the pedagogical conditions for their effective learning at university. Particular attention is paid to the need for individualization of the educational process, the creation of a nurturing learning environment, and the use of active teaching methods. It is noted that developing the potential of gifted students is an important task for modern higher education, as this category of students possesses the high intellectual and creative potential necessary for the scientific, technological, and social development of society.
Keywords: giftedness, gifted students, higher education, individualization of learning, educational environment, development of personal potential.